Influence of Chronic Kidney Disease on Patients Undergoing Elective Hip and Knee Orthopedic Surgery: A Systematic Review and Meta-Analysis. Issue 3 (16th March 2021) - Zhang, Yijian; Shao, Yijie; Liu, Hao; He, Fan; Bou, Emily; Yang, Huilin; Pi, Bin
Abstract: Background : The increasing prevalence of chronic kidney disease (CKD) in recent years and its impact on renal dysfunction on orthopedic surgery continues to draw more attention to orthopedic surgeons. The purpose of this study is to investigate the influence of CKD on comorbidities and complications in patients who underwent elective low limbs surgery. Material and Methods : Until August 2018, Pubmed, Embase, Cochrane library, and Web of science were used to search relevant literature. After reviewing the article title, the abstract, and the full text, a total of 11 articles were identified in the qualitative synthesis. Demographic data, comorbidities, and complications were assessed between CKD and non-CKD patients. Review Manager 5.3 was used for the statistical analysis, and forest plots were constructed for each variable. Results : A total of 137, 436 patients (10, 732 patients with CKD and 126, 704 patients without CKD) from 11 studies were enrolled in this meta-analysis. CKD patients showed worse health conditions in comparison to non-CKD patients. The incidence of several preoperative comorbidities (hypertension, diabetes, and cardiac-cerebral disease) and postoperative complications (infection, transfusion, deep vein thrombosis, and early mortality) were higher in CKD patients. Conclusions : In elective hip and knee surgery, compared with non-CKD patients, CKD patients showed worse health conditions. Due to a higher rate of comorbidities and complications in CKD patients, they should be treated carefully during perioperative periods.